Effects of a large-scale alcohol ban on population-level alcohol intake, weight, blood pressure, blood glucose, and domestic violence in India: A quasi-experimental population-based study - Chakrabarti, Suman; Christopher, Anita; Scott, Samuel P.; Kishore, Avinash; Nguyen, Phuong Hong (Elsevier, 2024)
Background Globally, alcohol consumption is a leading risk factor for deaths and disability and a causal factor in over 200 diseases, injuries, and health conditions. In April 2016, the manufacture, transport, sale, and consumption of alcohol was banned in Bihar, a populous Indian state. We sought to estimate the impacts of this ban on health outcomes and domestic violence.